2002
DOI: 10.1016/s0006-291x(02)02751-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genes induced by BRCA1 in breast cancer cells

Abstract: Inherited mutations of the BRCA1 gene predispose to cancer of the breast, ovaries and other organs. The BRCA1 protein product is implicated in the maintenance of chromosomal integrity as BRCA1-deficient cells display gross chromosomal rearrangements. Chromosomal instability in BRCA1-deficient cells is related to inappropriate DNA double-strand break repair. The role of the BRCA1 gene in the maintenance of chromosomal integrity is linked to a number of biological properties of its protein product including tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 117 publications
1
39
0
Order By: Relevance
“…Previous studies have demonstrated that Erbin is a target of the tumor suppressor BRCA-1 and that loss of BRCA-1 and Erbin mRNA expression are correlated with a poor prognosis in early primary breast cancer (46,47). Erbin expression is also increased at the neuromuscular junction after denervation, suggesting that the protein levels of Erbin are regulated by neuronal activity (25).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that Erbin is a target of the tumor suppressor BRCA-1 and that loss of BRCA-1 and Erbin mRNA expression are correlated with a poor prognosis in early primary breast cancer (46,47). Erbin expression is also increased at the neuromuscular junction after denervation, suggesting that the protein levels of Erbin are regulated by neuronal activity (25).…”
Section: Discussionmentioning
confidence: 99%
“…Poly(A)+ RNA was subsequently isolated using Poly(A)+ spin columns (New England Biolabs). Subtraction PCR was performed with 2 μg poly(A)+ RNA for tester and driver using the PCR select system (Clontech), with the modifications previously described (55).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, OVCA1 has been identified as a BRCA1-inducible gene, using a forced BRCA1 overexpression assay in the MCF breast cancer cell line (Atalay et al 2002). BRCA1 mutations are associated with the formation of both breast and ovarian cancer (Gayther et al 1995).…”
Section: Genes and Development 327mentioning
confidence: 99%